DESENVOLVIMENTO DE UM MANUAL PARA CONTROLE GLICÊMICO DE RECÉM-NASCIDOS NAS PRIMEIRAS 48 HORAS DE VIDA - Martelli, Gicelle Moraes (2024)
The quality of health services has played an important role in reducing infant mortality rates. Considering perinatal care, neonatal hypoglycemia stands out, occurring in 5-15% of newborns in the first days of life. It is emphasized that neonatal hypoglycemia is usually asymptomatic, which is why professionals should be alert to possible clinical signs. Objectives: to identify the Knowledge, Attitude and Practice (KAP) on the assistance of multidisciplinary teams in monitoring blood glucose in the first 48 hours of the newborn's life; to build and validate a manual for monitoring blood glucose in the first 48 hours of life to recognize risk factors and the procedures followed in newborns who present hypoglycemia. Methodological path: the review included articles published between 2013 and 2023, in Portuguese and English, available in full text, excluding off-topic, non-free materials, theses, dissertations and ministerial documents. The search was carried out in the VHL/MEDLINE/LILACs, PubMed and ScienceDirect databases, using the descriptors “hypoglycemia”, “newborn” and “glycemic control” with the operator "AND”. The articles were selected following the PRISMA model and organized in tables containing title, authors, methodology, results and conclusions. Data analysis advanced in three stages: pre-analysis, analysis and interpretation. The main issues identified were neonatal hypoglycemia and glycemic monitoring strategies, with focus. in standards and practices to improve neonatal health. The second stage consists of a cross-sectional study, which used a Knowledge, Attitude and Practice (KAP) survey for nurses and doctors. data collection, and consisted of describing the preparation of a manual that followed the following steps: elaboration of the development project, search in the literature and transformation of the information found in the literature into an accessible language. The project was approved under opinion 6,768,532 Results: Ten articles that addressed the proposed theme were selected for the ILR. Most of them had level of evidence 2B. The ten studies reviewed presented varied methodologies. Diverging in relation to the reference values of glucose levels in newborns in the first hours of life, which reflects on the conduct and decision-making of multidisciplinary teams. Fifty professionals participated in the CAP survey, and it was identified that they know the risk factors, signs and symptoms of hypoglycemia, but there are gaps in relation to blood glucose levels and glycemic control. In terms of attitude, the most important answers were correct about breastfeeding and the use of dextrose, with disagreements regarding continuous control and conduct for blood glucose levels >47 mg/dl. In practice, there was consensus on topics related to breastfeeding, but responses varied regarding the administration of dextrose. It was observed that there was no statistically significant difference between the responses of nurses and physicians. The average number of correct answers was 0.50 ± 0.18. The manual developed was prepared with the commitment to collaborate with the professional practice of nursing, and is called “Clinical Manual: neonatal hypoglycemia in full-term newborns”. Information was selected and the content was presented objectively and complemented by selected images and colors. To make the material attractive and encourage consultation, the colors based on the triad of the color wheel were used: orange, aquamarine and purple, which were selected due to the harmony they create, combining primary and secondary tones. The manual covers neonatal hypoglycemia in the first 48 hours of a newborn's life, and addresses neonatal screening for the risk of hypoglycemia, clinical evaluation of the newborn and nursing diagnosis. Final Considerations: Finally, the literature review made it possible to observe gaps in the studies, highlighting the need for manuals and protocols that take into account the singularities of newborns. Furthermore, the practice of health professionals stands out when compared to knowledge and attitude, requiring moments of qualification, updating and mainly dialogue between professionals of multidisciplinary teams. With this, after the publication of the manual prepared, it is desired to reduce the number of unnecessary interventions with newborns at risk of neonatal hypoglycemia during the first 48 hours of life, as well as in the long term, to obtain a reduction in infant mortality rates.